Some Aspects of Environmental Quilombo Cruz in Talks about Environmental Resources Management - Da Silva, Wellington Amancio; Marques, Juracy; Da Silva, Wilma Amâncio; Amâncio, Maria Alice Vieira; Santos, Noeme Cabral da Silva (American Journal of Human Ecology, 2015)
This paper aims to reflect the environmental and praxis in satisfaction of the Brazilian semi-arid northeast, specifically in quilombola village Cruz; analyze their possible contributions to the epistemological reflection in the face of monoculture of knowledge as logic in overcoming process; the aim is still present some environmental aspects, the maroon community studied from the viewpoint of ecology of knowledge. If you do even a critique of the paradigms of the modern sciences, especially as the implications of reflection and scientific practice based on the Cartesian view of the world, given their methods, how to search, and especially the legitimizing discourse of impartiality as truth (Kuhn, 2009) research, objectified understanding of reality and their analysis. This article is based on extensive literature survey started in 2009 in the course of degree in Pedagogy (UNEB) and has continued until the present year, the Masters in Human Ecology and Environmental Management (UNEB / PPGEcoH).